2014
DOI: 10.1007/s00425-014-2047-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromium distribution in shoots of macrophyte Callitriche cophocarpa Sendtn.

Abstract: The aim of the study was the analysis of Cr distribution in shoots of the macrophyte Callitriche cophocarpa by means of two X-ray-based techniques: micro X-ray fluorescence (μXRF) and electron probe X-ray microanalysis (EPXMA). Plants were treated with 100 μM (5.2 mg l−1) chromium solutions for 7 days. Cr was introduced independently at two speciations as Cr(III) and Cr(VI), known for their diverse physicochemical properties and different influence on living organisms. A comparative analysis of Cr(III)-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…In our earlier work (Augustynowicz et al 2014 ), we demonstrated the different accumulation patterns of Cr in Callitriche mature leaves and stems incubated both in Cr(III) and Cr(VI) solutions. In the present paper, we focus on the differences between the young and mature organs.…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…In our earlier work (Augustynowicz et al 2014 ), we demonstrated the different accumulation patterns of Cr in Callitriche mature leaves and stems incubated both in Cr(III) and Cr(VI) solutions. In the present paper, we focus on the differences between the young and mature organs.…”
Section: Introductionsupporting
confidence: 49%
“…After treatment with Cr(VI)- and Cr(III)-containing media the plant samples were prepared according to a freeze-drying protocol to avoid the dehydration and redistribution of Cr ions during prolonged μXRF measurements (Augustynowicz et al 2014 ). The spatial distribution of chromium was investigated with a laboratory micro-XRF spectrometer (Wróbel et al 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Simulated studies using Cr(VI) as the spiking agent to investigate different crop reactions and growth have been reported by several authors [15,33,34]. Cr is considered strongly toxic because Cr(III) compounds in the soil are more or less insoluble and their ions are tightly bound to humus and clay particles while Cr(VI) is very soluble and easily passes through the plant cells into vacuoles where they combine with cations and form stable compounds which either accelerate or retard plants growth [34]. Amarantha dubuis Thell and Spinacia oleracea germinated in low concentration only while Cicer arietinum, Phaseoulus vulgaris and Vigna angularis germinated in both low and high concentration of Cr(VI).…”
Section: Effect Of Chromium Concentration On Seed Germination and Growthmentioning
confidence: 99%
“…It may be possible to state here that seed coats of different plants' impermeability and embryos' selectivity could have affected the tolerance The current study observed a significant variation in the germination and growth of edible vegetable seeds in Cr polluted soils (Figure 3c). Simulated studies using Cr(VI) as the spiking agent to investigate different crop reactions and growth have been reported by several authors [15,33,34]. Cr is considered strongly toxic because Cr(III) compounds in the soil are more or less insoluble and their ions are tightly bound to humus and clay particles while Cr(VI) is very soluble and easily passes through the plant cells into vacuoles where they combine with cations and form stable compounds which either accelerate or retard plants growth [34].…”
Section: Effect Of Chromium Concentration On Seed Germination and Growthmentioning
confidence: 99%
“…The Cr transported to the aerial parts or retained at the roots might have affected the physiological processes of plants growth as it contributed to their various reduction in height as shown in Figure 2. [28,14] Simulated studies using Cr (VI) as the spiking agent to investigate different crops reactions have been reported by [29,30,31]. Cr is considered strongly toxic because Cr (III) compounds in the soil are more or less insoluble and their ions are tightly bound to humus and clay particles while Cr (VI) is very soluble and easily pass through the plant cells into vacuoles where they combine with cations and form stable compounds which either accelerate or retard plants growth [32].…”
Section: 2: Effect Of Chromium Concentration On Seed Germination Anmentioning
confidence: 99%